Drei Aulos-Virtuosen aus Böotien: Antigenidas, Ismenias und Timotheos - Scheithauer, Andrea (Archiv für Musikwissenschaft, 2023)
In spite of some similarites, these three musicians were the embodiment of divergent virtuosic types owing to their diversified professional artistic identities and personas. Antigenidas was a performing musician, composer, and poet, in contrast to the predominantly cult musician, Ismenias. While Timotheos cultivated a traditional artistic image as a member of Alexander the Great’s court, Antigenidas and Ismenias worked for various patrons in different locations in the Greek world. Owing to his innovations, Antigenidas wielded the greatest influence on the aulos’s development and its music. Together with Ismenias, both musicians engaged in extravagant solistic presentations through increasingly elaborate optical and acoustic stagings, which led to a trend, viewed critically by the Principate, toward ever greater artistic excesses